Biodiversity Conservation and Phylogenetic Systematics: Preserving our evolutionary heritage in an extinction crisis - Pellens, Roseli; Grandcolas, Philippe (Topics in Biodiversity and Conservation, 2016)
Biodiversity; Nature conservation